Solar Radiation and Air and Ground Temperature Relations in the Cold and Hyper‐Arid Quartermain Mountains, McMurdo Dry Valleys of Antarctica. (7th August 2015) - Lacelle, Denis; Lapalme, Caitlin; Davila, Alfonso F.; Pollard, Wayne; Marinova, Margarita; Heldmann, Jennifer; McKay, Christopher P.
Abstract: This study compares the relations between solar radiation and air and ground temperatures in the Quartermain Mountains of the McMurdo Dry Valleys of Antarctica with those in ice‐free Victoria Land and Arctic Canada. The surface offset is near 0°C at all sites in the Quartermain Mountains and other sites in coastal Victoria Land, whereas the thermal offset is near 0°C at shallow ice table depths (< 20 cm) and near 1°C for ice tables deeper than the depth of diurnal temperature variation. The surface and thermal offsets in Victoria Land differ markedly from those in Arctic Canada, which are generally characterised by a positive surface offset and a negative thermal offset. These important differences highlight the effects of a lack of vegetation, surface organic layer, snow cover and moisture content in near‐surface soils on the direction and magnitude of surface and thermal offsets. Summer ground surface temperatures in the Quartermain Mountains correlate strongly with incoming solar radiation. Based on measured ground surface temperatures and modelled potential incoming solar radiation, two zones with distinct ground surface temperatures are defined in the Quartermain Mountains: (i) perennially cryotic zones (PCZs) characterised by ground surface temperatures always below 0°C; and (ii) seasonally non‐cryotic zones (NCZs) characterised by ground surface temperatures > 0°C for at least a few hours. Soils in the PCZs experience water exchange through vapour diffusion, whereas soils in the NCZs contain features associated with liquid water activity, such as increased soil moisture and frozen ponds recharged by snow/glacier meltwater. Copyright © 2015 John Wiley & Sons, Ltd.